Inter-American acquaintances (1917)
This little book makes no claim to completeness; its preparation by the author in the few spare moments of his life as a railway employe may perhaps excuse any fault of historical diction or exhaustiveness. It is intended to be suggestive rather than directly instructive,- to stimulate perhaps a few of those now engaged in studying South American history in its various phases in our colleges and universities to elaborate its material into historical or economic studies of permanent value. It aims to furnish proofs for the two following statements:- (I) That the moral and material aid and example of the United States were a factor in the Latin-American wars for independence; (2) That during that time, as well as previously, much was spoken and written by both North and South Americans which forecasted the Pan-American movement, embodying the fundamental ideas on which the Pan-American Union is based.